A Note on the Arc Elasticity of Demand - Gallego-Diaz, J. (Review of Economic Studies, 1944)
Journal Article A Note on the Arc Elasticity of Demand Get access J. Gallego-Diaz J. Gallego-Diaz Madrid Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 12, Issue 2, 1944, Pages 114–115, https://doi.org/10.2307/2296096 Published: 01 September 1944